Pelatihan Pembuatan Pupuk Cair Organik dan Kompos dari Limbah Sampah Rumah Tangga - Herniwanti, Herniwanti; Dewi, Oktavia; Rany, Novita; Nasyabila, Rafni (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: Buluh Cina Village is a tourist village located on the banks of the Siak River. The problem of waste among residents living on the banks of the river is throwing garbage directly into the river, causing water pollution. The purpose of this community service is to provide information on how housewives can manage household waste into liquid organic fertilizer (POC) and compost in a simple manner. Methodology: The method used was focus group discussion (FGD) on the theory of good waste management and a workshop demonstration of the practice of making POC and compost directly. This event was in collaboration with the health cadre partners of Puskesmas Pangkalan Baru and Buluh Cina village officials. Results: The results of this community service were attended by 31 cadres, who understood that the behavior of littering into the river must be stopped by utilizing waste from the household scale. POC and compost training, so it is hoped that cadres will apply to themselves and teach their members. Limitations: Owing to the limited time, funds, and members involved in this research, the training was only conducted for one day, but it is hoped that it will be sustainable. Contribution: This activity is useful to increase community awareness about managing household waste to make it more useful for fertilizing plants around the house and also have economic value if sold